Strategic Avoidance of General Anesthesia in Obstetric Trauma: Ear Ring Block for Auricular Reconstruction in a Second-Trimester Pregnancy - Purwoko; Septian Adi Permana; Fernando Feliz Christyan (Sriwijaya Journal of Otorhinolaryngology, 2025)
Background: Surgical interventions during pregnancy require balancing maternal physiological stability with fetal safety. Trauma necessitating ear reconstruction typically requires general anesthesia, which carries elevated risks of difficult airway management, aspiration, and fetal neurotoxicity. The “Ring Block” offers a regional alternative, yet evidence on its safety in second-trimester trauma remains limited. Objective: To evaluate the safety, hemodynamic stability, and surgical efficacy of a landmark-based Ear Ring Block as an alternative to general anesthesia for extensive auricular trauma reconstruction in a high-risk, second-trimester parturient. Case presentation: We present a 41-year-old multigravida at 14 weeks of gestation (ASA II) with a complex traumatic laceration of the right auricle following a motor vehicle accident. Owing to her advanced maternal age and the risks of general anesthesia, an awake ear reconstruction was planned using a landmark-based Ear Ring Block with 12 mL of 2% Lidocaine. Complete surgical anesthesia was achieved with a V-pattern and inverted V-pattern injection trajectory. Intraoperative monitoring revealed hemodynamic stability with no fluctuations in mean arterial pressure or fetal heart rate abnormalities. The patient reported a visual analog scale score of zero intraoperatively and was discharged 12 hours after surgery without complications. Conclusion: The Ear Ring Block represents a superior anesthetic modality for auricular trauma in pregnant patients. It effectively mitigates the physiological risks of general anesthesia while providing profound analgesia and hemodynamic stability. This technique should be considered a primary anesthetic strategy for auricular reconstruction in the obstetric population.